Demography and commonly recorded clinical conditions of Chihuahuas under primary veterinary care in the UK in 2016 - Dan G. O’Neill (BMC Veterinary Research, 2020)
Abstract Background The Chihuahua, the world’s smallest dog breed, is a popular breed in the UK today. The VetCompass™ Programme collates de-identified clinical records from primary-care veterinary practices in the UK for epidemiological research. This study aimed to characterise the demography, age at death and common disorders of Chihuahuas under primary veterinary care during 2016 in the UK. Results Chihuahuas comprised 11,647/336,865 (3.46%) dogs under veterinary care during 2016. The annual proportional birth rate for Chihuahuas rose from 1.01% in 2005 to 5.35% in 2016. Median adult bodyweight was 3.4 kg (interquartile range [IQR]: 2.7–4.3, range 0.8–9.8).). Median age was 2.8 years (interquartile range [IQR] 1.6–4.9). Median age at death from this young expanding population was 8.2 years (IQR 3.5–12.1). Females (10.2 years) outlived males (6.9 years) (Mann-Whitney U test: P = 0.005). The most common grouped causes of death were heart disease (18.8%, 95% CI: 10.9–29.0), lower respiratory tract disorder (16.3%, 95% CI: 8.9–26.2) and traumatic injury (13.8%, 95% CI: 7.1–23.3). The most common specific disorders were periodontal disease (13.5%, 95% CI: 12.6–14.4), obesity (5.9%, 95% CI: 5.3–6.5), retained deciduous dentition (5.7%, 95% CI: 5.1–6.4), anal sac impaction (4.9%, 95% CI: 4.4–5.5) and aggression (4.2%, 95% CI: 3.7–4.8). Among the 28 most common fine-level disorders, males had statistically (P <  0.005) higher probability than females for 5 disorders (aggression, heart murmur, otitis externa, conjunctivitis and upper respiratory tract infection). There were no disorders with statistically (P <  0.005) higher prevalence in females. Conclusions This study documented rising ownership and a currently youthful population of Chihuahuas in the UK. These results suggest that the Chihuahua is currently undergoing a popularity boom but veterinarians need to be watchful for welfare issues related to impulse purchase of Chihuahua puppies by owners with limited experience of dog care. Periodontal disease, obesity, retained deciduous dentition, anal sac impaction and aggression were identified as common health issues within the breed. The unique veterinary care needs of this popular miniature breed suggest that veterinarians should consider the value of advanced training in anesthesia and dentistry in small-sized dogs.